Corruption in Africa : effects on resource allocation and the role of leadership - (:unkn) unknown (My University, 2022)
This thesis proposes to study the relationship between corruption and African economies' current issues: state capacity, employment, and leadership. Thus, in the first chapter, the effects of corruption on the economic distribution of public expenditure are examined. The second chapter highlights the role of corruption in occupational choices. The third chapter examines the role of leaders in combating corruption.Several results emerge from these studies. (i) In terms of public spending, a high prevalence of corruption in Africa leads to a distortion of public expenditure away from capital spending. (ii) On employment, a new measure of public official's corruption is built as the difference between the salary perceived for a given position and the actual wage of the position. Thus, by overestimating the wage served in public administration in relation to corruption, job seekers choose to pursue a career in the civil service at the expense of other sectors. (iii) On the role of leaders, there is evidence of a substantial effect of the leadership of Captain Thomas Sankara and his anti-corruption policies on corruption in Burkina Faso from 1983 to 1987. Based on these results, and by way of recommendations, the thesis proposes: (i) to put the fight against corruption on the front page of development policies in Africa; (ii) make information on public administration, especially salary information, available to citizens and base the selection of public officials at least in part on anti-corruption characteristics; (iii) implement procedures relating to the integrity of leaders, and select leaders based on, among other things, their anti-corruption program.
Keywords: African Research